"How stupid can a person be?" – Students coping with authoritative dimensions of science lessons. (March 2020) - Kervinen, Anttoni; Roth, Wolff-Michael; Juuti, Kalle; Uitto, Anna
Abstract: Current mainstream practices of education tend to have an authoritative and serious side through their emphasis on the transmission and reproduction of canonical knowledge. Simultaneously, there are calls for dialogical approaches that provide students with opportunities to express their understandings and thereby increase engagement in learning. Yet there is little educational research on the students' ways of coping with the authoritative dimensions as these arise. In this study, we use data from an outdoor science setting where the teacher is not physically present to identify students' ways to act upon authoritative feedback. Our study shows that dialogic interactions among the students, which might be considered unacceptable behavior or off-topic activities, allow students to (temporarily) regain some level of control over the authoritativeness of teaching. The students use abusive language, humor and derision to oppose and degrade authoritativeness conveyed in the teacher's evaluative feedback in ways that would not be accessible to them with the teacher present. Simultaneously, disrupting the authoritative role of academic learning reinforced its serious nature, which manifests itself in the way that the students follow the teacher's instructions and improve their level of performance as if the negative emotions had been coped with in affectively meaningful ways.